Cost Comparison of a Traditional Didactic versus National Flipped Classroom Curriculum - Carbajal, Melissa M.; Karpen, Heidi; Arias-Shah, AnnaMarie; Gisondo, Carly; French, Heather M.; Gray, Megan M.; Izatt, Susan; Gillam-Krakauer, Maria; Johnston, Lindsay C.; Payne, Allison; Vasquez, Margarita M.; Bonachea, Elizabeth M.; Falck, Alison J.; Chess, Patricia R.; Dadiz, Rita (American Journal of Perinatology, 2024)
We compared the cost of faculty time preparing educational materials for traditional didactic (TD) education provided at local institutions with that of faculty time preparing National Neonatology Curriculum (NNC) flipped classroom (FC) educational materials shared among institutions for fellow education across the United States.Using survey data and the national average for faculty educators' salaries, we calculated the cost of developing TD versus FC materials. Wilcoxon rank-sum test and comparison of two Poisson rates were utilized to evaluate the time to create versus update TD materials and the cost to create new TD versus FC materials, respectively.FC materials required more time to develop than TD materials (FC, median 17 h, interquartile range [IQR]: 17; TD, median, 5 h, IQR: 5; p < 0.001). However, when the size of individual fellowship programs was factored into the cost analysis, FC materials shared nationally among programs resulted in a 19- to 72-fold cost savings when compared to the creation of new locally used TD materials (FC, $2.49 per fellow; TD $32.05–576.90 per fellow at very large-to-small fellowship programs; p < 0.001).Educational materials developed and disseminated to fellowship programs across the country confer significant savings in faculty educator time and cost per learner. Standardized programs such as the NNC may serve as a model to develop shared peer-reviewed educational resources for other specialties.
Keywords: cost analysis; didactic teaching; educator time; faculty time; flipped classroom; national curriculum; neonatal–perinatal medicine